2007
DOI: 10.1016/j.biomaterials.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Modulating bone cells response onto starch-based biomaterials by surface plasma treatment and protein adsorption

Abstract: The effect of oxygen-based radio frequency glow discharge (rfGD) on the surface of different starch-based biomaterials (SBB) and the influence of proteins adsorption on modulating bone-cells behavior was studied. Bovine serum albumin, fibronectin and vitronectin were used in single and complex protein systems. RfGD-treated surfaces showed to increase in hydrophilicity and surface energy when compared to non-modified SBB. Biodegradable polymeric blends of cornstarch with cellulose acetate (SCA; 50/50wt%), ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 55 publications
0
60
0
Order By: Relevance
“…The significance of this idea has been recognized for many years in the context of embryogenesis, where these forces are considered important to tissue ordering and morphogenetic movements (Beysens et al, 2000;Chen and Brodland, 2008;Foty et al, 1996). It has also been recognized in the context of biomaterials, where surface properties affect cell-implant interactions (Alves et al, 2007;Bren et al, 2004;Velzenberger et al, 2009). More recently, cell motions relevant to cancer metastases and tissue engineering have been explained in terms of cell surface tensions (Foty and Steinberg, 2004;Muller et al, 2007;Napolitano et al, 2007;Preetha et al, 2005;Siniscalco et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this idea has been recognized for many years in the context of embryogenesis, where these forces are considered important to tissue ordering and morphogenetic movements (Beysens et al, 2000;Chen and Brodland, 2008;Foty et al, 1996). It has also been recognized in the context of biomaterials, where surface properties affect cell-implant interactions (Alves et al, 2007;Bren et al, 2004;Velzenberger et al, 2009). More recently, cell motions relevant to cancer metastases and tissue engineering have been explained in terms of cell surface tensions (Foty and Steinberg, 2004;Muller et al, 2007;Napolitano et al, 2007;Preetha et al, 2005;Siniscalco et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental and theoretical investigations suggest that cell surface properties govern cell motions and tissue selforganization in settings that range from embryology to cancer to regenerative medicine (Alves et al, 2007;Brodland, 2004;Foty et al, 1996;Foty and Steinberg, 2004;Lecuit and Lenne, 2007;Liu et al, 2008;Muller et al, 2007;Napolitano et al, 2007;Preetha et al, 2005;Siniscalco et al, 2008;Steinberg, 2007;Velzenberger et al, 2009). As reviewed in Brodland (2004) and elsewhere, surfaceassociated proteins and other subcellular structural components give rise to net tensions along cell-cell and cell-medium interfaces.…”
mentioning
confidence: 99%
“…The SBBs selected are known to present different properties in terms of bulk chemistry, surface energy, wettability and phase interconnectivity (Alves et al 2003(Alves et al , 2007Pashkuleva et al 2005Pashkuleva et al , 2008. As part of previous research, their in vitro (Marques et al 2002) and in vivo biological response has been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…SPCL . SCA ranking in terms of hydrophobicity, with contact angles of 80.0 + 2.68, 78.80 + 1.78 and 76.4 + 3.38, respectively ( p , 0.05 for the comparison of SEVA-C and SCA contact angles) (Alves et al 2007). The contact angle variation between the different materials was low for all surfaces and values were above 658, which is considered to be the theoretical limit between hydrophobic and hydrophilic properties (Vogler 1998 onto hydrophilic substrates (Gessner et al 2000), whereas the majority have found that proteins tended to adsorb more extensively onto hydrophobic surfaces (Nakanishi et al 2001;Liu et al 2006) such as SBBs.…”
mentioning
confidence: 99%
“…It was found that adsorption of ECM proteins to the titanium surface was achieved. In 2007, Alves et al facilitated the adsorption of albumin and fibronectin on titanium plates using oxygen-based glow discharge plasma treatment 15) . Although these studies demonstrated that plasma modification clearly promoted the proliferation of osteoblastic cells, there was no direct evidence that the proteins chemically bound to the titanium surface.…”
Section: Introductionmentioning
confidence: 99%